Sven Linnér: Dostoevskij on Realism. Stockholm. (Uppsala), Almqvist & Wiksell, (1967). 279 p. 21,5 x 14,5 cm. (Acta Universitatis Stockholmiensis. Slavic Studies, 1). - Giménez Mathus, María Cristina (1969)
Fil: Giménez Mathus, María Cristina. Universidad Nacional de Cuyo